(untitled) (Northern International Medical College Journal, 2017)
Background : Premature infants frequently suffer from feeding intolerance and is highly associated to morbidity and mortality. It is a great challenge which have to face all the neonatologist. Feeding intolerance can be defined by difficulty in ingestion or digestion of the milk that causes a disruption in the enteral feeding plan due to the manifestation of some clinical symptoms. These symptoms include gastric residuals, emesis, abdominal distention, visible bowel loops, and change in the character of stool etc. Objective : To determine the frequency of feeding intolerance in hospitalized preterm neonates. Methods : This prospective study was carried out on preterm neonates admitted at neonatal intensive care unit of Padma General Hospital from 1st January 2016 to 31st December 2016. Inclusion criteria included Preterm infants of both genders from day 0 to day 28 of life and with gestational age (GA) of 28 to 36 weeks (estimated by 1st day of maternal last menstrual period). Diagnosis of feeding intolerance depends on presence of one or more signs that leading to interruption of the enteral feeding regime of the preterm. Results : The incidence of feeding intolerance in hospitalized preterm was 4.2% Conclusion : The percentage of feeding intolerance in our study is 4.2% of the preterm neonate. Northern International Medical College Journal Vol.8(1) July 2016: 178-180